BIODIVERSITY OF MARINE TUNICATES IN SAMALONA WATERS, SANGKARANG ARCHIPELAGO, INDONESIA - Litaay, Magdalena; Santosa, Slamet; Johannes, Eva; Agus, Rosana; Moka, Willem; Tanjung, Jennyta Dhewi Darmansyah (Hasanuddin University, 2018)
The study aims to know the biodiversity and community structure of marine tunicate in Samalona waters. The present study is part of biodiversity assessment for marine resources of Sangkarang Archipelago SW Makassar Indonesia. Field campaign was conducted from October to November 2016. Sample collection was done at 3 and 7 m depth by using Line Intersection Transect (LIT) method combined with a quadrat (plot). Two 50 m transects were placed parallel to a shore line at three stations (sta.) at Samalona waters. A quadrat (plot) (2.5 m x 2.5 m) was placed side by side of the line transect and all tunicates in the transect was recorded, identified, counted and photographed. Samples were collected by using SCUBA and under water camera. Environmental parameters including water temperatue, salinity, dissolved oxygen, clarity, current and wind speed, were measured in situ. Data were analysed using ecological indices including species composition and density, Shanon Wienner species diversity, Evenness, and Morisita Indices. The result indicates that there are 18 species of tunicates present at 3 m as well as 7 m depth of Samalona waters.. Result of the ecological analysis shows that species diversity can be categorized as moderate and there were no dominant species. Environmental parameters indicates that water quality at Samalona waters was in good condition to support tunicates.